2019
DOI: 10.3390/microorganisms7120693
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Amino Acids in Xanthomonas oryzae pv. oryzae Is Essential to Its Pathogenicity

Abstract: Xanthomonas oryzae pv. oryzae (Xoo) is the causal agent of rice bacterial blight disease, which causes a large reduction in rice production. The successful interaction of pathogens and plants requires a particular nutrient environment that allows pathogen growth and the initiation of both pathogen and host responses. Amino acid synthesis is essential for bacterial growth when bacteria encounter amino acid-deficient environments, but the effects of amino acid synthesis on Xoo pathogenicity are unclear. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…A Streptococcus pneumoniae IlvC mutant showed reduced survival, impaired BCAA biosynthesis and attenuated host colonization [21]. Studies with Xanthomonas oryzae showed that Leu can stimulate virulence-related response and regulates pathogenicity [22]. Similarly, studies with Xanthomonas campestris pv.…”
Section: Introductionmentioning
confidence: 99%
“…A Streptococcus pneumoniae IlvC mutant showed reduced survival, impaired BCAA biosynthesis and attenuated host colonization [21]. Studies with Xanthomonas oryzae showed that Leu can stimulate virulence-related response and regulates pathogenicity [22]. Similarly, studies with Xanthomonas campestris pv.…”
Section: Introductionmentioning
confidence: 99%
“…The Psa2 lrp gene was not modulated by minimal medium, suggesting that branched-chain amino acids regulate virulence via other pathways, as shown for Xanthomonas oryzae pv. oryzae(60). Leucine and valine are also precursors for the synthesis of diffusible signal factors (DSFs), which act as quorum sensing molecules.…”
mentioning
confidence: 99%
“…In Xoo, biosynthesis of amino acids such as leucine and arginine are essential to its pathogenicity. In addition, leucine could stimulate virulence-related responses and regulate Xoo pathogenicity [ 42 ]. GO-terms associated with PANTHER pathways showed leucine biosynthesis with the highest FE.…”
Section: Discussionmentioning
confidence: 99%